Search for nearly mass-degenerate higgsinos using low-momentum mildly displaced tracks in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review letters, 2024)
Higgsinos with masses near the electroweak scale can solve the hierarchy problem and provide a dark matter candidate, while detecting them at the LHC remains challenging if their mass splitting is 𝒪⁡(1 GeV). This Letter presents a novel search for nearly mass-degenerate Higgsinos in events with an energetic jet, missing transverse momentum, and a low-momentum track with a significant transverse impact parameter using 140 fb−1 of proton-proton collision data at √𝑠=13 TeV collected by the ATLAS experiment. For the first time since LEP, a range of mass splittings between the lightest charged and neutral Higgsinos from 0.3 to 0.9 GeV is excluded at 95% confidence level, with a maximum reach of approximately 170 GeV in the Higgsino mass.
Gesehen am 10.10.2025
ATLAS collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]